A 13.56-MHz RFID System Based on Organic Transponders. - Cantatore, E. (IEEE Journal of solid state circuits)
RFID tags based on organic transistors are described, discussing in detail the IC blocks used to build the logic and the radio. Tags energized and read out at 13.56 MHz, de facto standard frequency for item-level identification, have been tested and enabled for the first time multiple-object identification, using different 6-bit codes. A complete 64-bit transponder, the most complex organic RFID tag reported to date, operates at 125 kHz and employs 1938 transistors